2010
DOI: 10.1165/rcmb.2009-0118oc
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Dnaic1 in a Murine Model of Primary Ciliary Dyskinesia Causes Chronic Rhinosinusitis

Abstract: Studies of primary ciliary dyskinesia (PCD) have been hampered by the lack of a suitable animal model because disruption of essential ciliary genes in mice results in a high incidence of lethal hydrocephalus. To develop a viable mouse model for long-term studies of PCD, we have generated a transgenic mouse line in which two conserved exons of the mouse intermediate dynein chain gene, Dnaic1, are flanked by loxP sites (Dnaic1(flox/flox)). Dnaic1 is the murine homolog of human DNAI1, which is mutated in approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(115 citation statements)
references
References 44 publications
6
109
0
Order By: Relevance
“…4A). Clearance rates were measured during deep anesthesia and immediately after death because ciliary beat, and hence clearance, continues several hours postmortem (21). No significant differences in clearance rates were detected between the WT (1.69 ± 0.10 mm/min, n = 13) and Muc5ac-Tg (1.49 ± 0.17 mm/ min, n = 11) animals, suggesting the presence of a sufficiently hydrated mucus that is removed efficiently from the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…4A). Clearance rates were measured during deep anesthesia and immediately after death because ciliary beat, and hence clearance, continues several hours postmortem (21). No significant differences in clearance rates were detected between the WT (1.69 ± 0.10 mm/min, n = 13) and Muc5ac-Tg (1.49 ± 0.17 mm/ min, n = 11) animals, suggesting the presence of a sufficiently hydrated mucus that is removed efficiently from the surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…This mouse line has been constantly bred as a homozygous colony for over 50 years, demonstrating that it is robust, viable, and that it demands only normal husbandry, in contrast to the viability issues seen in other models including Dnahc5 [Tan et al, 2007], nm1054 [Lee et al, 2008] and the complex preparatory considerations associated with the Dnaic conditional mutant [Ostrowski et al, 2010]. We have not only confirmed that the iv model has static respiratory cilia at 37 • C, but that it develops PCD-related disease including rhinitis, sinusitis, and otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion, including Dnahc5 (MIM# 603335) [Tan et al, 2007], Poll (MIM# 606343) [Kobayashi et al, 2002], and Dnaic1 (MIM# 604366) [Ostrowski et al, 2010], demonstrate additional defects, particularly hydrocephalus and cardiac anomalies, reducing their viability and raising significant animal welfare issues. The repeated demonstration that mutation of human PCD loci in the mouse results in hydrocephalus has led some to suggest an underlying difference in physiology [Ibanez-Tallon et al, 2002;Ostrowski et al, 2010]. The nm1054 mouse (MGI: Del(1)1Brk), a six-gene deletion, gives rise to PCD-like upper respiratory pathology, lacks cardiac defects, and only shows hydrocephalus on certain genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovered pups were returned to their mother and those that developed hydrocephalus were sacrificed at P6 and P21 for analysis of differentiation in the SCN. Dnaic1 -/-mice (Ostrowski et al, 2009) were used as a genetic model for assessing the effects of hydrocephalus on SCN development and postnatal neurogenesis in the OB. The developmental time course of hydrocephalus in Dnaic1 -/-mice was similar to that in FoxJ1 -/-mice, starting between P1 and P6 with a progressive increase in ventricular volume by P21.…”
Section: Foxj1-independent Hydrocephalic Modelsmentioning
confidence: 99%